A responsabilidade do Estado pela irrazoável duração do processo judicial - Barbosa, Marcos Antônio Paderes (2010)
This study aims to analyze State liability arising from an infringement of the right to reasonable duration of court proceedings. Whereas the theme is recent in Brazilian law and given the lack of works about it, the searchs were subsidied in Spanish law, in French law, in Italian law and European Court of human rights. We discussed the right to "reasonable term" and also that kind of responsibility in the countries mentioned, and in their courts too. In all countries analysed the violation of this right results in State responsibility, with the consequent damages reparation. It was seen also the definition of justice deny. In our law, we have been studying the origins of speedy procedure . The tradition of the courts is to deny State liability due to judicial activity, with arguments like sovereignty, iudicata, independence of judges and fallibility, we refute them all, notably with the most recent courts decisions of the countries of the european continent. In conclusion, we figured out that we can blame the Brazilian State for damage caused by unreasonable duration of the process